The Influence of Entrepreneurship Character, Technology, and Financial Literacy on MSME Business Performance in Central Java and Yogyakarta - Kurnia Efendi; Faqiatul Mariya Waharini (Jurnal Analisis Bisnis Ekonomi, 2023)
This study examines the effect of entrepreneurial characteristics, use of technology, and accounting literacy on the business performance of Micro, Small, and Medium Enterprises (MSMEs) in Central Java and the Special Region of Yogyakarta (DIY). This study used 2,684 respondents from owners and managers of MSMEs in seven regencies and cities in Central Java and Yogyakarta. The data that has been collected is analyzed using WarpPLS. The result shows that entrepreneurial characteristics, use of technology, and accounting literacy positively and significantly impact business performance. These results have positive implications that MSMEs are able to achieve business performance by optimizing these three things.